Customers' risk tolerance and suppliers' investment inefficiency - Karel Hrazdil; Jeong-bon Kim; Xin Li (Journal of Risk and Financial Management, 2022)
We examine the effect of the risk tolerance of downstream firms (i.e., customers) on the investment inefficiency of upstream firms (i.e., suppliers). Using the pilot licensing status of the CEOs as a proxy for their inherent risk tolerance, we find that customer firms led by pilot CEOs are associated with suppliers' investment inefficiency, where investment inefficiency is more pronounced when the suppliers have less bargaining power over their customers. Our dynamic analysis confirms the causative relation between customer risk tolerance and supplier investment inefficiency and suggests that customers' risk tolerance plays a significant role in shaping suppliers' relationship-specific investment strategies.
Keywords: 330; risk tolerance; pilot; CEO; customer; supply chain; supplier inefficiency